The Cloning and Expression of Carboxyl Terminal Part of Protective Antigen from Bacillus Anthracis - Keyhan AH, Tahmasbpour Marzony E, Farhadi N, Kamali M (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Antibody production against to protective antigen (PA) can be helpful in immunotherapy and anthrax treatment. The carboxyl terminal part of PA has the most important playing in immune system induction. The objective of this study is cloning and recombinant expression of carboxyl site of protective protein for antibody production.METHODS: In this experimental study after DNA extraction from Bacillus anthracis, the presence of PA gene on bacterial chromosome was confirmed by PCR method. The site of carboxyl terminal from PA protein amplified by PCR method, then PCR productions and plasmid were cut out by BamH I and Hind III restriction enzymes. PCR production and plasmid transformed into E. coli BL21 (DE3). Clones containing gene of interest was determined by PCR reaction, enzyme digestion and sequencing. Moreover, the production of recombinant proteins was confirmed by SDS-PAGE and western methods.FINDINGS: The sequence of carboxyl terminal part of PA was confirmed by sequencing, PCR and enzymatic digestion method which suggestion to intended gene cloning in E. coli BL21 (DE3). SDS-PAGE and western blotting confirmed the production of recombinant protein with 20 KD in molecular weight.CONCLUSION: According to the results of this study, this recombinant protein can be produced in high levels by this method, which opens a new window for vaccine and monoclonal antibody production against the intended disease.